Assessment of organochlorine pesticides in different seaweed species of Thoothukudi coast, Tamil Nadu, South India - Sundhar, S.; Jeyashakila, Robinson; Jeyasekaran, Geevaretnam; Aanand, S.; Shalini, R. (Indian Journal of Fisheries, 2021)
Five species of macroalgae, namely Sargassum wightii, Padina tetrastromatica, Ulva lactuca, Caulerpa racemosa and Gracilaria edulis collected from three sampling sites, viz. Harbour Beach (site 1), Tharuvaikkulam (site 2) and Hare Island (site 3), situated along the Thoothukudi region of the Gulf of Mannar were analysed for 17 organochlorine pesticides (OCPs) by gas chromatography-mass spectrometry (GC-MS) to assess their suitability as biomonitors of pesticide contamination. The total OCP concentrations were several folds higher in all the macroalgae collected from site 1 than in the other two sites. Brown alga S. wightii accumulated more OCPs (297 ng g-1) than the other sampled algal species in site 1. The OCPs assessed in this study were endrin aldehyde (51 ng g-1), endrin (48 ng g-1), Î² hexachlorocyclohexane (45 ng g-1), heptachlor epoxide (43 ng g-1), dichlorodiphenyldichloroethylene (37 ng g-1) and endosulfan sulfate (11 ng g-1) in S. wightii. It was observed that the green alga C. racemosa had selective sorption of endosulfan I (43 ng g-1) and red alga G. edulis had selective sorption of endosulfan II (44 ng g-1). The ability of seaweeds to accumulate pesticides was found to be species specific and not class specific. The study indicated that S. wightii could be used as a biomonitor of OCP residues in the marine environment, withthe exception of endosulfan.Keywords: Endosulfan, Macroalgae, OCPs, Pesticides